Fig. 2. A in Gastrointestinal helminths of waterfowl (Anatidae: Anatinae) in the Lerma marshes of central Mexico: Some pathological aspects - Padilla-Aguilar, Patricia; Romero-Callejas, Evangelina; Jos; Ramírez-Lezama, e; Osorio-Sarabia, David; García-Prieto, Luis; Manterola, Carlos; García-M, Luis Jorge; arquez; Zarza, Heliot (Zenodo, 2020)
Fig. 2. A. Proventriculus section of Oxyura jamaicensis showing a T. fissispina gravid female in the lumen of the glandular epithelium, surrounded by some giant cells (asterisk), lymphocytes and wrapped by a fibrous vascular connective tissue capsule (arrow) that displaces the proventriculus glands. Stained with H-E. B. Proventriculus of Mareca americana, showing multiple inflammatory foci consisting of lymphocytes and a few eosinophils. The cestode Gastrotaenia cygni can be observed on the glands' lumen. Stained with H-E. C. Anas acuta gizzard, where the presence of abundant nematodes (Epomidiostomun uncinatum and Amidostomum spp.) can be observed below the keratinized epithelium, surrounded by an abundant amount of mucus (asterisk) and hyperplasia of the mucus-producing cells (arrow). Stained with H-E. D. Gizzard of Anas crecca, where nematodes of the genus Amidostomum can be observed below the keratinized epithelium surrounded by an abundant amount of mucus (arrow). Stained with Masson's trichromic. Published as part of Padilla-Aguilar, Patricia, Romero-Callejas, Evangelina, Jos, Ramírez-Lezama, e, Osorio-Sarabia, David, García-Prieto, Luis, Manterola, Carlos, García-M, Luis Jorge, arquez & Zarza, Heliot, 2020, Gastrointestinal helminths of waterfowl (Anatidae: Anatinae) in the Lerma marshes of central Mexico: Some pathological aspects, pp. 72-79 in International Journal for Parasitology: Parasites and Wildlife 13 on page 77, DOI:10.1016/j.ijppaw.2020.07.008, http://zenodo.org/record/13241707